A Comprehensive Overview of Dynamic Line Rating Combined with Other Flexibility Options from an Operational Point of View - Erdinc, F. Gulsen; Erdinc, Ozan; Yumurtaci, Recep; Catalao, Joao P. S. (MDPI, 2020)
The need for flexibility in power system operation gradually increases regarding more renewable energy integration, load growth, etc., and the system operators already invest in this manner to enhance the power system operation. Besides, the power system has thermally sensitive assets such as lines, transformers, etc. that are normally operated under highly conservative static ratings. There is a growing trend in this regard to use the actual capacity of such assets dynamically under varying operating conditions leading to a dynamic thermal rating concept which is referred as dynamic line rating (DLR) approach specifically for lines. This study provides a comprehensive overview of existing perspectives on DLR and combination with other flexibility options from an operational point of view. Apart from the existing review studies more focused on implementation category of DLR concept, the concentration on more operational stage from the power system operation point of view leads the difference of this study compared to the mentioned studies. A categorization of the DLR implementation for either being sole or combined usage as a flexibility option is further realized. Besides, a geographically categorized analysis on existing practical evidence on DLR concept and implementations is also presented in this study.
Keywords: dynamic line rating; flexibility; operational perspective; overhead lines; CONSTRAINED UNIT COMMITMENT; TRANSMISSION-LINES; WIND POWER; CONGESTION MANAGEMENT; SYSTEM; RELIABILITY; RISK; GENERATION; PENETRATION; AMPACITY; Energy & Fuels